Cardiac sarcoidosis recurrence post-heart transplant: A critical literature and case report - Salotti, Andrea; Mondini, Lucrezia; Confalonieri, Paola; Salton, Francesco; Nalli, Chiara; Reccardini, Nicolò; Torregiani, Chiara; Antonaglia, Caterina; Hughes, Michael; Confalonieri, Marco; Cifaldi, Rossella; Ruaro, Barbara (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Recurrence of cardiac sarcoidosis (CS) following heart transplantation (HT) is a rare but clinically significant complication that influences management strategies and prognosis. This review examines existing evidence on the diagnosis and treatment of post-transplant CS recurrence. Additionally, we present a case report of CS recurrence in a patient after HT. Methods: We analyzed clinical studies, case reports, and systematic reviews published up to January 2025, focusing on the recurrence of CS after transplantation. Results: Limited data suggest that immunosuppressive therapies are crucial in managing post-transplant CS recurrence. Diagnosis relies on imaging modalities such as Positron Emission Tomography (PET-CT), Cardiac Magnetic Resonance (CMR), and endomyocardial biopsies. Treatment generally involves intensifying immunosuppressive therapy. Conclusions: Standardized guidelines are essential to improve the management of this rare and complex condition and to enhance long-term patient outcomes.